Analyzing the Impact of Workers' Remittances on Savings and Total Deposits: A Study of Economic Dynamics - Mahesh Joshi (HM Journals, 2024)
This study investigates the impact of workers' remittances on savings and total deposits within the context of economic dynamics. Employing quantitative analysis, the research aims to elucidate the intricate relationship between these variables and their. Using data sourced from Nepal Rastra Bank spanning from June 2017 to April 2024, key variables including gross foreign exchange reserves, total trade balance, workers' remittances, and balance of payments deficit are examined. The research employs the Autoregressive Distributed Lag (ARDL) model alongside diagnostic tests to analyze both long-term and short-term relationships among the variables. Results reveal significant long-run relationships between workers' remittances and both savings and total deposits, indicating a positive influence of remittances on financial intermediation and capital accumulation. Granger causality tests suggest predictive causality between savings and workers' remittances, as well as between workers' remittances and total deposits, underscoring the importance of remittance inflows in shaping financial behaviors. However, other causality directions do not show significant effects, suggesting complex interdependencies among these variables. The findings support the main hypothesis that workers' remittances have a significant impact on both savings and total deposits in the long run. This research contributes to a deeper understanding of the economic dynamics driven by workers' remittances and provides valuable insights for policymakers, financial institutions, and stakeholders involved in economic development strategies.